Analysis of Phenolic and Flavonoid Contents, and the Anti-Oxidative Potential and Lipid Peroxidation Inhibitory Activity of Methanolic Extract of Carissa opaca Roots and Its Fractions in Different Solvents - Dildar Ahmed; Khaizran Fatima; Ramsha Saeed (MDPI AG, 2014)
The objective of the present work was to investigate the anti-oxidative potential of methanolic extract of Carissa opaca roots and its fractions in solvents of different polarities. Total phenolic (TPC) and flavonoid (TFC) contents of methanolic extract were 211.95 ± 0.78 μg/mL gallic acid equivalents (GAE) and 8.35 ± 0.21 μg/mL rutin equivalents (RE), respectively. Ethyl acetate contained the highest amounts of both (TFC, 11.8 ± 0.28 RE; TPC, 342.80 ± 0.42 GAE) followed by chloroform fraction (TFC, 7.50 ± 0.14 RE; TPC, 275.85 ± 0.50 GAE). Extract and fractions displayed remarkable DPPH radical scavenging activity. EC50 values of methanolic extract was 0.88 mg/mL, while that of hexane, chloroform, ethyl acetate, n-butanolic and aqueous fractions were 0.58, 0.38, 0.29, 0.36 and 5.83 mg/mL, respectively, ethyl acetate fraction being most potent. The ethyl acetate fraction also showed the highest activity in terms of reducing power, phosphomolybdate and ABTS assays. All the fractions showed fairly good lipid peroxidation inhibitory activity, which remained almost constant over three days. Based on the results it can be concluded that roots of Carissa opaca contains phytochemicals with exploitable antioxidant, free radical scavenging, and lipid peroxidation inhibitory potential.